Chloride Transport in Concrete Subjected to Electric Field - Buenfeld, Nick R; Glass, Gareth K; Hassanein, Alaa M; Zhang, Jian-Zhong (Journal of materials in civil engineering, 1998)
Chloride transport in concrete is often subject to an electric field. This may arise from an internal source, such as the development of a membrane potential, or it may be imposed on the concrete by an external source, as is often the case when electrochemical remediation techniques are applied and accelerated chloride diffusion tests are undertaken. In this work the theory of chloride migration and its practical applications are reviewed. The migration of ions in an electric field differs from other transport processes in that positive and negative ions move in opposite directions, and the condition of electroneutrality does not impose the same constraint on the transport of ions as would otherwise be the case. Well established laws with appropriate boundary conditions have been used to model chloride transport in concrete under electrochemical chloride extraction and cathodic protection conditions, as well as in accelerated chloride diffusion tests. The minimum electric field that will prevent further chloride contamination may be regarded as the threshold requirement for chloride removal and also provides a basis for a corrosion prevention measure in its own right. The quantification of the membrane effects of concrete on the transport of chloride ions and the time dependence of chloride binding and dissolution require further research.